Psychosocial factors influencing dietary management in patients with type 2 diabetes and healthy adults: an ecological momentary assessment approach - Saito, Junichi; Kumano, Hiroaki (Frontiers in Psychology, 2025)
Background: Dietary management in diabetic patients is affected by psychosocial factors and the socialenvironmental context. Ecological momentary assessment (EMA) allows patients to consistently report their experiences in real-time over a certain period and across different contexts. Despite the importance of dietary management, only a few EMA studies have been conducted on dietary management and psychosocial factors in patients with type 2 diabetes; further evidence must be gathered. Therefore, this study examined dietary management and psychosocial factors using EMA, comparing type 2 diabetes patients with healthy adults.Methods: A total of 20 patients with type 2 diabetes and 16 healthy adults underwent EMA. Relying on event-contingent recordings, this study evaluated the participants' mood (e.g., anxiety, anger, vigor), appetite (hunger, craving), meal types (e.g., breakfast), location (e.g., eating out), companions (e.g., family), and dietary lapses (e.g., I ate a larger portion of a meal or snack than I intended) before and after meals. Dietary lapse recording after meals was paired with psychosocial data before meals. Only the type 2 diabetes patients used a sensor-based glucose monitoring system (Freestyle Libre Pro, Abbot) and wearable activity monitors (GT3X-BT, ActiGraph).The EMA produced a total of 4254 responses. Dietary lapse predicted two-hour postprandial glucose through a sensor-based glucose monitoring system. Multilevel logistic regression analyses were performed. For diabetes patients, dietary lapse was affected by vigor, fatigue, and cravings before eating. Meanwhile, for healthy adults, only fatigue before meals affected dietary lapse, and increased vigor from dietary intake was associated with dietary lapse. In both type 2 diabetes patients and healthy adults, eatingout situations were linked to dietary lapse. The results suggest differences in psychosocial factors influencing dietary lapse between patients with type 2 diabetes and healthy adults. EMA is well suited to assess psychosocial factors that drive dietary management in diabetic patients. This study further discussed the possibility of individual approaches using EMA data.